Salinization in the Co Chien river and solutions for river fresh water exploitation to supply for Tra Vinh city - Vinh, Dang Hoa; Thuc, Pham Thi Bich (Vietnam Journal of Earth Sciences, 2012)
Domestic water supply in the coastal Mekong Delta provinces in general and in Tra Vinh in particular is very stressful. At present, water source for domestic water supply is mainly from groundwater. However,  groundwater is now being over-exploited which leads to aquifer salinization, land subsidence, etc. In the future, domestic water demand will continue to rise so that groundwater can not meet the demand. Therefore, it is very urgent to look for alternative water sources.This article introduces the analysis and assessment of capabilities to exploit Co Chien river freshwater at the Tra Vinh hydrological station and reconstruction of the abandoned Lang The river into a reservoir, which is capable of providing domestic water for Tra Vinh city